2002
DOI: 10.1051/0004-6361:20020778
|View full text |Cite
|
Sign up to set email alerts
|

XMM-Newton observations of the isolated neutron star RX J0806.4-4123

Abstract: Abstract. The isolated neutron star RX J0806.4-4123 was observed with XMM-Newton in November 2000. The data from the three EPIC instruments allowed us (i) to derive an improved X-ray position to an accuracy of 2-3 , (ii) to accumulate the first medium-resolution soft X-ray spectra of high statistical quality and (iii) to find a candidate for the neutron star rotation period. Although this period of 11.3714 s is formally detected at a 3.5σ level in the EPIC-pn data, the similar pulse profiles deduced from all t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 26 publications
2
28
0
1
Order By: Relevance
“…We used a Bayesian odds ratio (Gregory & Loredo 1996;Haberl et al 2008) and a Rayleigh Z 2 1 (Buccheri et al 1983;Haberl & Zavlin 2002) Since this period has a significance of 3.3σ and could not be confirmed in the other observations, probably owing to the lower number of detected counts, the spin period needs further confirmation.…”
Section: Analyses and Results Of X-ray Observationsmentioning
confidence: 99%
“…We used a Bayesian odds ratio (Gregory & Loredo 1996;Haberl et al 2008) and a Rayleigh Z 2 1 (Buccheri et al 1983;Haberl & Zavlin 2002) Since this period has a significance of 3.3σ and could not be confirmed in the other observations, probably owing to the lower number of detected counts, the spin period needs further confirmation.…”
Section: Analyses and Results Of X-ray Observationsmentioning
confidence: 99%
“…The same holds for the Swift data (2.5 s frame time). A χ 2 test, a Bayesian odds ratio (Gregory & Loredo 1996), and a Rayleigh Z 2 test for one harmonic (Haberl & Zavlin 2002;Buccheri et al 1983) around the periodicity signal are shown in Fig. 5.…”
Section: Pulsationsmentioning
confidence: 99%
“…In particular, a substantial contribution of ROSAT to this field has been the discovery of a group of seven radioquiet, close-by, thermally-emitting INSs, dubbed ROSAT INSs (RINSs) and sometimes referred to as the "magnificent seven" (see for recent references Treves et al 2000;Zampieri et al 2001;Haberl & Zavlin 2002; see also Popov & Prokhorov 2003). The nature of these sources has been controversial and two interpretations were proposed, either as conventional middle-aged cooling NSs or as very old NSs accreting the Send offprint requests to: S. B. Popov, e-mail: polar@sai.msu.ru interstellar gas (see again Treves et al 2000).…”
Section: Introductionmentioning
confidence: 99%